THE EFFECT OF SERVICE QUALITY ON LOYALTY, THROUGH CUSTOMER SATISFACTION AT REGION DEVELOPMENT BANK OF PAPUA LLC BRANCH AGATS - Santoso, Yesica Theresia; Rachmawati, Ike Kusdyah; Handoko, Yunus (Universitas Nusa Cendana, 2025)
Customer loyalty is formed from a feeling of satisfaction with the services provided by employees or officers who are in a position to provide excellent service to every customer who visits. Satisfaction can be felt if someone experiences more than they expected. The overall experience is one of the elements of the establishment of loyalty to a company. The purpose of this study was to analyze the effect of service quality on customer loyalty through customer satisfaction as intervening. The population in this study was civil servants who made credit more than twice, with a total sample of 40 respondents. The sampling technique used was purposive sampling, and the analysis method used was path analysis with the Sobel test using the SPSS 29 data processing application. The results of this study indicate that (1) Service Quality has a direct positive and significant effect on Customer Satisfaction of on Customer Satisfaction of Regional Development Bank of Papua LLC Branch Agats; (2) Customer Satisfaction has a positive and significant direct effect on Customer Loyalty; (3) Service Quality has a positive and significant indirect effect on Customer Loyalty through Customer Satisfaction. The results showed that service quality has a direct and significant effect on customer satisfaction, customer satisfaction has a direct and significant effect on loyalty, and service quality has a significant effect on customer satisfaction directly and significantly on loyalty, and service quality has a significant effect on loyalty through customers. Keywords: Service Quality; Loyalty; Customer Satisfaction